Ecolopes, beyond greening. A multi-species approach for urban design - Maria Canepa; Francesca Mosca; Shany Barath; Alexandre Changenet; Thomas E. Hauck; Ferdinand Ludwig; Enrica Roccotiello; Marta Pianta; Surayyn Uthaya Selvan; Verena Vogler; Katia Perini (Agathón)
Urbanisation, due to its contribution to climate change and loss of biodiversity, damages ecosystems, thereby affecting human health and well-being. Current urban and architectural design approaches, that aim to reduce the environmental impact of buildings, include, among other strategies, the integration of greening systems but focusing primarily on the potential benefits for humans. Other organisms such as animals and microbiota and the self-dynamic development of plant communities, which could play a central role in increasing biodiversity, are not considered in the planning process. This paper describes how the ECOLOPES project overcomes this strictly anthropocentric view, developing a systematic design approach for architecture in a multi-species perspective to create regenerative urban ecosystems.